The Main Forms of Academic Cheating in Educational Practices of Ukrainian Students - Pak, Inna (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The article is devoted to appearance causes and prevalence level analysis of a "crib" as a form of academic dishonesty, the degree and peculiarities of its distribution in the Ukrainian higher education. The phenomenon of academic culture of students as a multicomponent phenomenon is described, which contains various types of formal and informal practices, educational and scientific activities are the major of them. The understanding of the academic culture of the students as an indicator of the state of the higher education system of Ukraine is substantiated. It allows to analyze the educational process in the general context of academic integrity (decency), that is a central element and a peculiar foundation for the academic culture and all its subjects. The historical experience of student use some forms of academic cheating is described. The impact of academic dishonesty on the quality, efficiency, and competitiveness of the entire education system is analyzed. The causes of widespreading the practice of cheating and using of cribs are described according to sociological researches "Academic Culture of Ukrainian Students: The Main Factors of Formation and Development", "Ukrainian Higher Education Reforms in the Assessments of the Participants of the Educational Process" and the All-Ukrainian Monitoring Survey "Ukrainian Teachers and the Learning Environment (TALIS)". It is determined that the origins of the practice of academic cheating originate in secondary school. Despite the fact that writing-off is perceived by all subjects of the educational process as a deviation from the norms of academic culture, but in the Ukrainian educational space, it is customary everyday practice and one of the components of learning. It is concluded that determining the factors that influence the positive attitude of students towards writing-off, will allow us to understand ways to overcome this problem and will provide an opportunity to identify productive quality sanction measures against violators of academic integrity. The most important, it will change the attitude of students and all subjects of academic culture to the violation of the norms of academic integrity.